LOW-COST, LOAD CELL AND MICROCONTROLLER BASED BENDING STIFFNESS TESTER - KAPUSI, Z.; TUNYAGI, A.; SIMON, A. (Studia Universitatis Babeș-Bolyai Physica, 2019)
Paper and paperboard have many applications, from writing, printing and householding to packaging. Bending stiffness is probably the most important mechanical property of paper and paperboard, it provides rigidity in some industrial processes like printing or folding. The present work describes the design and implementation of a low-cost bending stiffness tester proposed as a graduation project for Engineering Physics students. The performances of the device were successfully tested on both certified and real-life paper products.